MEMBANGUN KEMAMPUAN BERPIKIR KRITIS SISWA SD MELALUI PEMBELAJARAN MATEMATIKA PENGUKURAN DENGAN PROJECT BASED LEARNING BERBASIS LINGKUNGAN - Mardiana Anjani Alamsyah; Lailatul Hidayati; Siti Inganah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking is an individual's ability that involves aspects of analysis and reasoning to solve a problem. In this context, critical thinking is an important skill that needs to be trained from an early age, one of which is understanding the concept of mathematics learning, because learning mathematics requires critical thinking, especially in measurement material. Mathematics learning must emphasize understanding concepts through direct experience. The use of environmental media in learning is a contextual learning resource for students, especially in measurement material using non-standard units. The surrounding environment provides a variety of real objects that help students practice measurement concepts so that they are easy to understand. This simple research aims to describe the mathematics learning process using environmental media using the Project Based Learning model to improve students' critical thinking skills in measuring length, weight or volume using non-standard units such as spans, steps or seeds. This research originates from information or assistance in mathematics learning measurement material from class 2 which was carried out on Wednesday, October 9 2024.